Dermatitis in humans caused by Ornithonyssus bursa (Berlese 1888) (Mesostigmata: Macronyssidae) and new records from Brazil - Bassini-Silva,Ricardo (2019)
Abstract Ornithonyssus bursa, known as the “tropical fowl mite”, is a hematophagous mite of domestic and wild birds, occasionally biting humans. Infestation on humans occurs mainly when the abandoned nests are close to homes, or by manipulation of infested birds by humans. In Brazil, this species occurs in the south and southeast of the country. In the present study we are reporting bites on humans, new localities records, host associations, and molecular information of O. bursa.